The Role of Emotion Regulation and Socialization in Behavioral Parent Training: A Proof-of-Concept Study. Issue 1 (January 2019) - Zachary, Chloe; Jones, Deborah J.; McKee, Laura G.; Baucom, Donald H.; Forehand, Rex L.
Low-income families are less likely to effectively engage in Behavioral Parent Training (BPT), the standard of care for early-onset (3-8 years old) disruptive behavior disorders (DBDs); however, relatively little is known about predictors of treatment process and outcome within this vulnerable group. Given literature to suggest compromises associated with both low-income status and DBDs, this study examined the role of caregiver emotion regulation and socialization practices in 15 low-income families who participated in one evidence-based BPT program, Helping the Noncompliant Child (HNC). Findings suggest baseline caregiver emotion regulation predicted variability in BPT treatment duration and outcomes, whereas baseline caregiver emotion socialization practices explained variation in the severity of child disruptive behaviors concurrently, as well as BPT treatment outcomes. Furthermore, BPT yielded pre- to posttreatment effect sizes that were equivalent to or better than treatments designed to more explicitly target emotion regulation and socialization processes. Clinical implications and future directions are discussed.